THE ESSENCE OF LANGUAGE INTERFERENCE IN LEARNING GERMAN (Scientific journal of the Fergana State University, 2024)
This article discusses theoretical issues and the study of the phenomenon of language interference, which manifests itself in the study of the German language. In this case, the individual plays an important role in the violation of linguistic norms, in particular the use of linguistic elements in oral and written speech, as well as changes that occurred as a result of the mutual influence of the Uzbek and German languages, arising in the process of linguistic communication in which there are two different types of influence of the native language on the linguistic system of the language being studied, that is, if both languages have identical meanings in phonetic, lexico-semantic and grammatical structure, the studied language is easier to learn, and significant differences at all linguistic levels of both languages lead to the manifestation of language interference.